Penguatan Kemampuan Siswa Berpikir Kreatif Melalui Model Pembelajaran Snowball Throwing Dengan Motivasi Belajar - Intan Ratnasari; Zainul Abidin; Henry Praherdhiono (Universitas Negeri Malang, 2021)
This study aims to determine the effect of the Snowball Throwing learning model on students' ability to think creatively. This study used a quasy experimental design with a sample random sampling model. The subject of this research was grade 8 MTs Raudlatul Ulum Karangploso. The instrument used in determining the enthusiasm for learning was a questionnaire, while to determine the students' ability to think creatively, students used an essay test. For the results of the study, the value of the experimental class is greater than the control class in all assessments, including the two-way ANOVA results also have Fcount greater than Ftable. Show that the Snowball Throwing learning model and enthusiasm affect the students' ability to think creatively.AbstrakPenelitian bertujuan untuk mengetahui pengaruh model pembelajaran Snowball Throwing terhadap kemampuan pebelajar berpikir kreatif pebelajar. Penelitian menggunakan quasy experimental design dengan model sample random sampling. Subjek penelitian ini adalah kelas 8 MTs Raudlatul Ulum Karangploso. Instrumen yang dipakai dalam mengetahui semangat belajar adalah angket sedangkan untuk mengetahui kemampuan pebelajar berpikir kreatif pebelajar memakai tes essay. Untuk hasil penelitian lebih besar nilai dari kelas eksperimen daripada kelas kontrol di segala penilaian, termasuk pada hasil ANAVA dua arah juga memiliki Fhitung yang lebih besar daripada Ftabel. Menunjukkan bahwa model pembelajaran Snowball Throwing dan semangat mempengaruhi kemampuan pebelajar berpikir kreatif pebelajar.